Renaissance of Islam: A Content Analysis of Muhammad Rashīd Riḍā’s Exegesis - Hamim, Khairul; Abdillah, M Masykur (Journal of Islamic Thought and Civilization, 2023)
The current study aimed to investigate the concepts of Islamic Revival in the light of Rashīd Riḍā’s interpretation. This study was guided by a single research question. The research question focused on the exegesis of the Islamic Renaissance according to the teachings of Rashīd Riḍā. The current study comprised a library research that employed text documents as its data sources. The primary sources of the data included two monumental works by Rashīd Riḍā namely Tafsīr al-Manārand Majallah al-Manār (al-ManārMagazine). In the meantime, pertinent journal articles and scientific books provided the secondary data for the current study. Content analysis was used as an analytical approach. The words, sentences, and paragraphs related to the theme of the current study were examined in depth. Moreover, the study also demonstrated that Rashīd Riḍā’s exegesis of the Islamic Renaissance has five dimensions. Firstly, the emphasis on the purity of Islam; secondly, the prohibition of blind imitation (taqlīd); thirdly, the emphasis on a rational approach to the interpretation of the Qur’ān; fourthly, the emphasis on ijtihād; and fifthly, the incorporation of modern knowledge. This study contributes to the dissemination of valuable insights in order to address the complex problems encountered by Muslim societies and the world as a whole in the modern age.